PEMROGRAMAN RENCANA ANGGARAN BIAYA PEMBANGUNAN KAPAL - Hutauruk, Ronald Mangasi; Pandiangan, Wandy Leo; Syaifuddin, Syaifuddin (Jurnal Perikanan dan Kelautan, 2015)
Accuration for preparing budget to estimate contruction costs greatly affects thesuccess of its funding. In addition, this will effect the successfull of its building. Inboatbuilding project, this will monitor the initial funding ability. Therefore,preparation of Cost –Budget Plan (RAB) can be as a solution to describe total cost inboatbuilding as material cost, cost of manpower, etc. The aim of this research is togenerate application of RAB for Bagansiapi-api shipyard by using Macros Excel. It isdeveloped by using prototype methods with visual basic for application (VBA).Results shown that the resulting aplication can help in processing the boatbuildingcost .